SOUND AND SEMANTIC CHANGE IN LANGUAGE BORROWING : THE CASE OF MINANGKABAU WORD BORROWED INTO INDONESIA - Surahman Abdi; Fitrawati Fitrawati (Universitas Negeri Padang, 2018)
Borrowing word is one way of overcome vocabulary that does not exist in the destination language. In addition, word borrowing is used to enrich vocabulary in a language. Borrowing vocabulary can happen from local language to national or foreign language, and the reverse happens. The purpose of this paper is to know the words borrowed from the local language (Minangkabau) into the national language (Bahasa Indonesia). This research focuses only on the sounds and shifting of meaning. Many of the words in detail are 70 words out of a total of about 929 words (8.71%) accompanied by source from KBBI. In word borrowing from Minangkabau language to Indonesian there are 25 (38,71%) words that are adopted in its entirety, and 45 words (64.29%) words that go through the process of adjustment of meaning and rules (adaptation). there are 2 words that experience narrowing meaning and 1 word experiencing the expansion of meaning. It can be concluded that there are two vocabulary borrowing processes from the Minangkabau language to the language without changing the core meaning of the word. Both processes are adoption and adaptation.